Daviborshch's cart : narrating the Holocaust in Australian war crimes trials - Fraser, David 1953- (University of Nebraska Press, 2010)
Introduction : the long and winding road from Ukraine to Australia -- History, war crimes, and law in Ukraine -- A brief political and legal history of Australia and Nazi war criminals -- Law and history in Australian war crimes trials : Ukrainian foresters, the Shoah, and the Polyukhovich case -- Mikolay Berezowsky : the case of "The witness who knew too much" -- The story of Daviborshch's cart : law, history, truth, and the Holocaust in Ukraine -- Translating law, translating history, in Australian war crimes trials -- Telling stories about the Shoah : perpetrators, victims, and the politics of Australian identity in The Hand That Signed The Paper -- Law, memory, and justice : the Australian experience